2017
DOI: 10.3389/fmicb.2017.00373
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of the Silkworm As an Animal Model for Developing Novel Antimicrobial Agents

Abstract: The demand for novel antibiotics to combat the global spread of multi drug-resistant pathogens continues to grow. Pathogenic bacteria and fungi that cause fatal human infections can also kill silkworms and the infected silkworms can be cured by the same antibiotics used to treat infections in the clinic. As an invertebrate model, silkworm model is characterized by its convenience, low cost, no ethical issues. The presence of conserved immune response and similar pharmacokinetics compared to mammals make silkwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Experiments using the silkworm evaluation system revealed that the viscous component of natto has a suppressive effect against sucrose-and glucose-induced hyperglycemia. Silkworms are useful for large-scale in vivo evaluation because they are inexpensive and can be reared in large groups (21)(22)(23)(24)(25)(26)(27). We reported the discovery of several active substances that suppress postprandial hyperglycemia using the silkworm evaluation system (4,11,28).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using the silkworm evaluation system revealed that the viscous component of natto has a suppressive effect against sucrose-and glucose-induced hyperglycemia. Silkworms are useful for large-scale in vivo evaluation because they are inexpensive and can be reared in large groups (21)(22)(23)(24)(25)(26)(27). We reported the discovery of several active substances that suppress postprandial hyperglycemia using the silkworm evaluation system (4,11,28).…”
Section: Discussionmentioning
confidence: 99%
“…91 The literature revealed that AMPs are a key component for immune defense against bacterial infection in silkworm. 7,87,[92][93][94][95][96] These observations stipulate that production of AMPs in silkworm through the Toll and IMD pathway is absolutely critical and remains unresolved. Hence, there is a need for detailed studies to understand such mechanisms, which will aid in providing more powerful tools against pathogenic multi-drugresistant microbes.…”
Section: Attacinmentioning
confidence: 99%
“…1a), identied by screening in a silkworm infection model. 8,9 It inhibited transcription in Staphylococcus aureus by binding to the primary sigma factor, SigA, and a single point mutation (D201N) in SigA was responsible for resistance to GPI0363. 8 However, the mechanism of how it inhibits transcription was not fully understood.…”
Section: Introductionmentioning
confidence: 99%